Effective lightweight, flexible and ultrathin PVDF/rGO/Ba2Co2Fe12O22 composite films for electromagnetic interference shielding applications. (1st September 2021) - Anand, S; Pauline, S
Abstract: In this study, we developed a simple and cost-effective solvent film casting method to fabricate ultrathin, flexible and lightweight polyvinylidenefluoride (PVDF)-based composites that provide high electromagnetic interference (EMI) shielding performance. Y-type barium hexaferrite with general formula Ba2 Co2 Fe12 O22 was first synthesized by the sol–gel autocombustion method and then reduced graphene oxide (rGO) was prepared by modified Hummer's method. The crystal structure, morphology, elemental surface analysis and magnetic properties of the samples were systematically investigated using x-ray diffraction spectroscopy, Fourier-transform infrared spectroscopy, Raman spectroscopy, high-resolution scanning electron microscopy, energy-dispersive x-ray spectroscopy, x-ray photoelectron spectroscopy and vibrating sample magnetometry. Then, the complex permittivity, complex permeability and EMI shielding properties of the flexible PVDF/rGO/Ba2 Co2 Fe12 O22 composite films with two different amounts of Ba2 Co2 Fe12 O22 NP content and a fixed amount of rGO content were investigated using a vector network analyzer. The structural characterizations of the resultant composite films showed the formation of an electroactive β -phase of PVDF with addition of Ba2 Co2 Fe12 O22 nanoparticles and rGO content. The enhancement of the β -phase in the PVDF/rGO/Ba2 Co2 Fe12 O22 nanocomposites was explained from a physicochemical viewpoint. Furthermore, the electrically conductive and magnetic properties of PVDF composite films incorporating rGO and Ba2 Co2 Fe12 O22 NPs exhibited a high EMI shielding effectiveness of 25.63 dB, with an absorption-dominated shielding feature in the 8–12 GHz region. The enhanced absorption was attributed to the electrostatic interaction induced by the β -phase fraction in the PVDF matrix, and subsequently from multiple reflections and magnetic loss originating from the synergetic effect of rGO and Ba2 Co2 Fe12 O22 NPs. This study introduces a low-cost and scalable method for the design of novel, lightweight, flexible and efficient EMI shielding composite films with promising prospects for application in the construction, electronics and aerospace fields.